E.H.C Game / Nurul Aisyah Mohd Anowar … [et al.] - Mohd Anowar, Nurul Aisyah; Wahab, Rosilah; Mohd Yusoff, Erna Suhana; Mazri, Nur Syafiqah; Mat@Adnan, Nurul Hidayah (Division of Research and Industry Linkages, 2017)
E.H.C (eye-hand coordination) game is a game that need high concentration and also need others cognitive components. This game also creates a stage for player to establish and to improve in their physical aspects and also in the cognitive aspects. One of the effect of poor hand-eye coordination is it can greatly compromise ability to exercise and can also affect everyday tasks such as writing and this can causing student to be diagnosed with a learning disability. The E.H.C can be uses as an intervention tool for special needs children who have difficulty in fine motor skills, attention and postural stability such as Attention Deficit Hyperactive Disorder (ADHD), Down syndrome and Developmental Delay. E.H.C game was designed to improve mental in aspect of cognitive level and also physical which is (i) To enhance fine motor skills involving small muscles of the hands and fingers, (ii) To develop eye-hand coordination which require eyes and hands to execute activities in simultaneous, (iii) To improve attention span and concentration of the child during activity, and (iv) To increase hand dexterity for a more precise grip. Furthermore, it has 3 different levels that a player must be completed and it also has grading which is from easy level to the more difficult. In conclusion, E.H.C game is suitable for those children that age from 5-17 years old, especially for special needs children.